“Buscando para ello testigos falsos” - Cunill, Caroline (Universidad Santiago de Cali, 2022)
Oral testimonies and, specially, those of Native people were often key pieces in the trials brought into Spanish America’s Courts of justice. In many cases, they are also the only sources available to capture indigenous voices in the Colonial archive. Nevertheless, although its centrality for our understanding not only of the Spanish Empire’s system of justice but also the records on which our historical narratives are built, little attention has been paid to this issue. This chapter aims at analyzing the production and use of indigenous oral testimonies in the Court of the governor of Yucatan, as well as its subsequent evaluation in the Council of the Indies in sixteenth century Spain. Building upon the trial relative to the transport of tributes by Maya tamenes (1573-1579), we will examine how witnesses were selected and their statements taken, and how those proofs were evaluated in court. Special attention will be paid to the ways in which pressure was exercised on witnesses.